Dream analysis using theories of analytical psychology - Buzaitė, Saulė (Psichologija, 1998)
The paper covers three major theoretical approches on dreams that now dominate in analytical psychology. Modifications of Jung’s original ideas could create some problems dealing with dream material to those who are not familiar with the present situation so the purpose of this paper is to clear up the pecularities characteristic to each theoretical approach. Clinical case report and qualitative data analysis forms methodological basis of the three level interpretation of dreams selected during the course of depth oriented psychotherapy. This method was chosen as the most appropriate dealing with the clinical material.